PENGARUH ZONASI TERHADAP ARUS MASUK PESERTA DIDIK BARU DI SMA MUHAMMADIYAH SURAKARTA - Punarsih Punarsih; Mohamad Ali (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2019)
Zoning is the process of accepting new students by considering the proximity of the house, or place of residence, to the education unit. This study seeks to understand the effect of zoning on the inflow of new students SMA Muhammadiyah Surakarta, and how the managers and organizers responded. Data collection methods in this study include the method of observation, interview methods, and documentation methods. Data analysis in this study used a quantitative and qualitative mix method. The results showed the effect of zoning policy on the inflow of new students in SMA Surakarta is variation. There was a slight decrease in new students in SMA Muhammadiyah 1. But there was an increase in SMA Muhammadiyah 2, Muhammadiyah 3, and Muhammadiyah Program Khusus Kottabarat Surakarta. The headmaster of SMA Muhammadiyah 2 and SMA Muhammadiyah Program Khusus Kottabarat Surakarta gave a positive response. Whereas the management of the SMA Muhammadiyah 1 and the Muhammadiyah 3 were less accepting because they were considered to be killing a private school. The Dikdasmen Council considers zoning policies to be unfair for private schools because it frees prospective students to choose 4 public schools at once, if not accepted in public schools, prospective new students will choose private schools